Asceticism and embodiment: female bodies, sexuality, and religious experiences in contemporary Russian women's writing. Issue 1 (2nd January 2022) - Hristova, Maria
ABSTRACT: This article examines the religious turn that has developed since 2000 in Russian women's writing, featuring strong female protagonists who seek spiritual enlightenment or enrichment through asceticism, usually in marginal spaces. The author focuses on Tat′iana Mazepina's travelogue, "Puteshestvie v storonu raia" ("Traveling to Paradise, " 2012) and Elena Koliadina's novel Tsvetochnyi krest ( The Flower Cross, 2011), two very dissimilar works by authors from different generations that both explicitly engage with aspects of Russian Orthodoxy. In these works, the female protagonists achieve a moment of transcendence by leaving behind their established lives and giving up physical comforts and sexual pleasure: one by following the female pilgrim trope, the other by becoming a holy fool and, later, a hermit. In this way, identity-formation and meaning-creation for these protagonists remain within a larger Orthodox community and cosmology, but outside the direct jurisdiction of the Church. Consequently, the protagonists do not perceive their behaviour as rebelling against or subverting traditional Christian ideas about gender roles and sexuality. Rather, their experiences of spirituality are presented as an alternative, parallel way of being, modelled after established narratives of female ascetics, in opposition to the ultrasexualized secular image of femininity prevalent in Russian popular culture.